Pengembangan Leaflet Dikaji dalam Dimensi Bernalar Kritis di Kelas IV SD Negeri 39 Pontianak Kota - Aisha, Hulul; Kresnadi, Hery; Bistari, Bistari (AS-SABIQUN, 2023)
The general objective of this research is to find out the leaflet development process which is studied in the dimension of critical reasoning on data and opportunity analysis elements in class IV SD Negeri 39 Pontianak Kota. The method used is Research and Development (RnD) by adopting the ADDIE development model. The data source in this study was a homeroom teacher, 32 students and 2 expert validators. Data collection techniques in this study were interviews, questionnaires and observation. The results of the research show that leaflet development is studied in the dimension of critical reasoning through three research steps, namely analysis, design, development. Researchers conducted a needs analysis and curriculum analysis. The steps taken at the design stage were to determine indicators of learning achievement and to design leaflet designs. Based on the results of the data obtained at the development stage, the feasibility of the leaflet development product is reviewed in the critical reasoning dimension obtaining the "very valid" criteria from the validator expert, namely in the presentation aspect getting an average of 5.00, in the design and graphic aspects the average is 4.92, and the material aspect has an average of 4.88. As well as the results of the response obtained the criteria of "very good" that is, on a small scale the average is 4.52 and large-scale trials get an average of 4.34.